Fiduciaries and trust : ethics, politics, economics and law / edited by Paul B. Miller, Matthew Harding. - Miller, Paul B. (Law teacher); Harding, Matthew, 1974- (Cambridge University Press, 2018)
Systematic analysis of fiduciaries and trust is rare. The aim of this volume is to help fill this gap. The chapters explore the interactions of fiduciary law and trust, drawing on literatures on trust that have been generated in a variety of disciplines. They do so with an eye to the full scope of extension claimed for the fiduciary principle, from its heartland in private law, to its frontiers in public law and government more broadly. Overall, the volume advances an integrated and wide-ranging understanding of the relation of fiduciaries and trust that illuminates key legal and political problems, and challenges and deepens our understanding of fiduciaries and trust themselves.